2002
DOI: 10.1046/j.1540-8167.2002.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Osborn Waves Associated with Ventricular Fibrillation in a Patient with Vasospastic Angina

Abstract: A 52-year-old man with a history of vasospastic angina experienced a severe ischemic episode accompanied by a non-Q wave myocardial infarction. Two episodes of ventricular fibrillation (VF) occurred during the acute phase of the event. Osborn waves were observed on the ECG preceding each episode of VF. In the second episode, the gradual development of Osborn waves until VF occurred was confirmed on ECG. The Osborn waves appeared to be related to the occurrence of VF. This case may provide clinical evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 5 publications
4
30
0
2
Order By: Relevance
“…In most cases, acute myocardial ischemia induced prominent J waves with a merged steeply down-sloping ST segment in the inferior and/or lateral leads (9,11) which are very close to the ECG pattern as observed in Brugada syndrome: coved type ST elevation (1, 2, 11). Numerous ionic currents, calcium cycling, signal transduction, and so forth would be altered during the myocardial ischemia but, both channelopathy and ischemia may share common mechanisms which result in such prominent J waves and coved type ST elevation, which may be risk factors which develop into ventricular fibrillation due to phase 2 reentry (8,13,18,19).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In most cases, acute myocardial ischemia induced prominent J waves with a merged steeply down-sloping ST segment in the inferior and/or lateral leads (9,11) which are very close to the ECG pattern as observed in Brugada syndrome: coved type ST elevation (1, 2, 11). Numerous ionic currents, calcium cycling, signal transduction, and so forth would be altered during the myocardial ischemia but, both channelopathy and ischemia may share common mechanisms which result in such prominent J waves and coved type ST elevation, which may be risk factors which develop into ventricular fibrillation due to phase 2 reentry (8,13,18,19).…”
Section: Discussionsupporting
confidence: 66%
“…Maruyama et al (9) reported a case of spastic angina pectoris in whom J waves (Osborn waves) developed during an ischemic attack. The amplitude of the Osborn waves increased spontaneously and this was followed by ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond hypothermia, other conditions have been reported to cause Osborn waves, such as hypercalcemia [7], brain injury [8], subarachnoid haemorrhage [9], cardiopulmonary arrest from oversedation [10], vasospastic angina [11], or idiopathic ventricular fibrillation [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Osborn waves are most commonly observed in hypothermia (hypothermic hump). However, some other conditions including hypercalcaemia, damage to the brain, cardiac arrest, Chagas disease, ischaemic heart disease and Brugada syndrome have been reported to cause J waves [2,3]. Below a temperature of 30°C, the J waves are detectable in 80% of patients [4].…”
mentioning
confidence: 99%